PENGARUH APLIKASI QUIZIZZ TERHADAP HASIL BELAJAR MATEMATIKA PADA PESERTA DIDIK DI MAN KOTABARU - Hartini R Tobo; Rahmi Yuliana M; Emi Kusumowati (STKIP Paris Barantai, 2023)
The purpose of this research is 1) to find out whether the use of the Quizizz application in learning mathematics affected the learning outcomes of students in class XI IPA MAN Kotabaru 2) to find out how much influence the use of the Quizizz application had in learning mathematics on the learning outcomes of students in class XI IPA MAN in Kotabaru. This type of research is experimental research with a quantitative approach. The research design is a Pre-Experimental Design One Group Pretest-Posttest Design. A sample of 36 students and data analysis techniques using descriptive analysis and inferential statistics. The results of the study are: 1) The use of the Quizizz application in learning mathematics has an effect on the learning outcomes of students in class XI IPA MAN Kotabaru seen from the results of testing the hypothesis using the t test, obtained tcount > ttable = 3.798705 > 2.030108 then H0 is rejected and H1 accepted, 2) The effect of using the Quizizz application (X) in learning mathematics on learning outcomes (Y) of students in class XI IPA MAN Kotabaru is 86% while the remaining 14% is influenced by other factors. Keywords: Influence, Quizizz Application, Mathematics Learning Outcomes